Prasugrel versus ticagrelor in patients with Acute Coronary syndrome treated with percutaneous coronary intervention - Jamwal, Naveen; Tripathi, Shiv Shanker (International Journal of Research in Medical Sciences, 2018)
Background: No association studies for the efficacy and safety of ticagrelor vs. prasugrel have been published in India. Aim of the study was to compare the safety and efficacy of Prasugrel versus Ticagrelor in Patients with Acute Coronary Syndrome Treated with Percutaneous Coronary Intervention. Methods: This retrospective study was designed to compare the efficacy and safety of prasugrel and ticagrelor in acute coronary syndromes (ACS) with percutaneous coronary intervention (PCI). A total of 480 patients were studied who had been prescribed either prasugrel or ticagrelor during PCI. Primary end-point was defined as death, re-infarction, urgent target vessel revascularization, serious bleeding requiring transfusion. Results: Primary endpoint was different between the groups receiving prasugrel and ticagrelor (1.2% and 4.0%, respectively; OR (95% CI) 0.38 (0.098; 1.43); P=0.065). Difference was found in the need for urgenttarget vessel revascularization which was significantly lower in the prasugrel group.Rest of the parameters were almost similar with no significant difference. Conclusions: This study comparing prasugrel and ticagrelor shows that Prasugrel is more effective than Ticagrelor in lowering ischemic events in the acute coronary syndromes treated with PCI strategy, especially incidence of stent thrombosis. These observations need further analysis and follow-up.